2020
DOI: 10.1177/1073191120975130
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Validation of the Levenson Self-Report Psychopathy (LSRP) Scale in a High-Risk Dutch Community Sample

Abstract: The Levenson Self-Report Psychopathy (LSRP) scale is a self-report measure that can be used to assess psychopathic traits in community samples, and recent research suggested that its three-factor model (Egocentricity, Callousness, and Antisocial) has promising psychometric properties. However, no study to date has validated the LSRP in a longitudinal framework. The present study sought to validate the LSRP scale in a longitudinal design using a sample of Dutch emerging adults ( ns = 970 and 693 at time points … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
11
1
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 70 publications
4
11
1
11
Order By: Relevance
“…The internal reliability values of the callousness and antisocial LSRP subscales were rather low, which might be due to the small number of scale items (e.g., Taber, 2018 ). Still, these levels are comparable to that of other studies ( Wissenburg et al, 2020 ), and still exceeding the generally accepted level of >0.50 ( Watkins, 2017 ). Inter-correlations between the study variables are shown in Table 2 .…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The internal reliability values of the callousness and antisocial LSRP subscales were rather low, which might be due to the small number of scale items (e.g., Taber, 2018 ). Still, these levels are comparable to that of other studies ( Wissenburg et al, 2020 ), and still exceeding the generally accepted level of >0.50 ( Watkins, 2017 ). Inter-correlations between the study variables are shown in Table 2 .…”
Section: Resultssupporting
confidence: 87%
“…The LSRP is a preferable psychopathy measure in general population samples, given that its focus does not lie on rather pathological, explicit, and overt antisocial behavior ( Garofalo et al, 2019 ). Although originally containing 26 items ( Levenson et al, 1995 ), we used the 19- items version that has been shown to be superior in reflecting the LSRP three-factor model of psychopathy, i.e., egocentricity, callousness, and antisociality ( Garofalo et al, 2019 ; Wissenburg et al, 2020 ). The 19 items were scored on a 4-point Likert scale ranging from 1 (completely disagree) to 4 (completely agree).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Las propiedades psicométricas de la LSRP han sido estudiadas en varios países como Bulgaria (Psederska et al, 2020), China (Wang et al, 2018), Estados Unidos de América (Brinkley et al, 2008;Lynam et al, 1999;Miller et al, 2008), Francia (Maheux-Caron et al, 2018, Italia (Somma et al, 2014), Nueva Zelanda (Sellbom, 2011), Países Bajos (Garofalo et al, 2019;Wissenburg et al, 2022), Portugal (Coelho et al, 2010 y España (Andreu-Rodríguez et al, 2018;Camacho-Guerrero et al 2011). Los resultados de dichos estudios se discuten a continuación.…”
unclassified
“…En general, la LSRP muestra adecuados indicadores de confiabilidad y de validez concurrente con otras pruebas como la PCL-R y el PPI (Salvador et al, 2016). Asimismo, también las puntuaciones de escala se mantienen bastante estables después de un periodo de 18 meses (Wissenburg et al, 2022).…”
unclassified